Gabon : Technical Assistance Report-Public Investment Management Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2020)
The development of infrastructure is one of the pillars of the Emerging Gabon Strategic Plan (PSGE). Implemented as of 2012, the PSGE has been establishing priority strategic guidelines to transform Gabon into an emerging economy by 2025. Its primary aims are to ensure and expedite the country's sustainable development and growth by focusing on potential growth sectors. Public investment grew continuously from 2009 to 2013, when it peaked at 15.2 percent of GDP; it averaged 5.7 percent growth from 1990 to 2018. At the same time, private investment declined, as did growth and public capital stock. These outcomes indicate that public investment in Gabon does not drive growth and that investment expenditure does not automatically translate into actual accumulation of assets, which raises questions about the efficiency of those outlays.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet